Lumbar Vertebral Canal Diameters in Adult Ugandan Skeletons (Tanzania Medical Journal, 2009)
Background: Normal values of lumbar vertebral canal diameters are useful in facilitating diagnosis of lumbar vertebral canal stenosis. Various studies have established variation on values between different populations, gender, age, and ethnic groups. Objectives: To determine the lumbar vertebral canal diameters in adult skeletons according to gender, ethnicity, and vertebral levels at Galloway osteological collection of Makerere university. Methods: A descriptive cross-section study was carried out on 216 complete sets of male and female human lumbar vertebral bones. The midsagittal, transverse diameters of the lumbar vertebral canal and the anteroposterior diameter of the inferior vertebral notch were measured using an electronic digital caliper. Collected data was analyzed using SPSS 12.0 computer program. Results and discussion: In both sexes, the midsagittal diameter of the canal was wider at the cephalic than at the caudal end; reflecting the size of the contents at this level and also an adaptation to ensure protection of these contents during complex movements of this transition region . A steady widening of the transverse diameter of the canal from L1 to L5 was also observed in both genders. The anteroposterior diameter of inferior vertebral notch was subject to gender and ethnic variation. Conclusion: The narrowest midsagittal diameter is found at L3 in both genders, the widest transverse diameter on the other hand was at L5. Various diameters of the lumbar vertebral canal varied according to gender and ethnicity. Tanzania Medical Journal Vol. 23 (2) 2008: pp. 28-30